2022
DOI: 10.1042/cs20220245
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation in rats induces dysfunction of placental leucine transport and alters fetal brain growth

Abstract: Maternal infection during pregnancy increases the offspring risk of developing a variety of neurodevelopmental disorders (NDDs), including schizophrenia. While the mechanisms remain unclear, dysregulation of placental function is implicated. We hypothesised that maternal infection, leading to maternal immune activation and stimulated cytokine production, alters placental and yolk sac amino acid transport, affecting fetal brain development and thus NDD risk. Using a rat model of maternal immune a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 81 publications
2
14
1
Order By: Relevance
“…Therefore, it may be that in our study, female offspring experienced a reduction in growth prenatally, causing postnatal behavioural adaptations to increase maternal resource solicitation behaviours such as USVs. Indeed, data from this model has recently demonstrated sex-specific effects in placental function which would support this, including a more pronounced reduction in amino acid transport in female placentas at GD16, compared to males (Kowash et al, 2022).…”
Section: Mia Induced Sex Differences In Early Postnatal Offspring Dev...mentioning
confidence: 70%
See 3 more Smart Citations
“…Therefore, it may be that in our study, female offspring experienced a reduction in growth prenatally, causing postnatal behavioural adaptations to increase maternal resource solicitation behaviours such as USVs. Indeed, data from this model has recently demonstrated sex-specific effects in placental function which would support this, including a more pronounced reduction in amino acid transport in female placentas at GD16, compared to males (Kowash et al, 2022).…”
Section: Mia Induced Sex Differences In Early Postnatal Offspring Dev...mentioning
confidence: 70%
“…Both IL-6 and TNFα have been shown to be induced during the maternal response to poly I:C and mediate downstream offspring developmental deficits (Murray et al, 2019;Smith et al, 2007). Recent data from our own validation of this model has demonstrated that both maternal IL-6 and TNFα plasma concentration peak at 2-3 h posttreatment with this source of poly I:C in pregnant Wistar rats, which is not seen for other canonical pro-inflammatory cytokines such as IL-1β (Kowash et al, 2022). Therefore, their concentration was measured in maternal plasma at baseline (pre-pregnancy) and 3 h post-treatment using rat-specific ELISAs for IL-6 and TNFα (ab100772 and ab100784 respectively, Abcam, UK).…”
Section: Maternal Cytokinesmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, Leucine is the most typical amino acid involved in autophagy regulation, it could activate downstream ULK-1 (Ubiquitin-like proteins-1) and Beclin-1, and then facilitate autophagosome formation following their interaction with LC3 (microtubule-associated protein light chain 3) ( Russell et al, 2013 ). Several studies have demonstrated that Leucine enters the brain from the blood more rapidly than any other as a nutritionally essential amino acid ( Yudkoff et al, 2005 ; Duan et al, 2016 ), and it competes with kynurenine for blood-to-brain transport and prevents lipopolysaccharide-induced depression-like behavior in mice ( Walker et al, 2019 ), and even maternal immune activation induces dysregulated placental transport of Leucine affecting fetal brain development in rats ( Kowash et al, 2022 ). Meanwhile, our previous result also found that there is an alteration of leucine content in both serum and feces of MS-induced irritable bowel syndrome rats.…”
Section: Introductionmentioning
confidence: 99%